Tourism Villages: Developing Tourist Attractions Based on Environmental Conservation For Sustainable Tourism - BELO, Odete; NEOLAKA, Melkisedek N.B.C; TODA, Hendrik (PT Keberlanjutan Strategis Indonesia, 2025)
Timor Leste has a Comissão Nacional da Eleiçoes body abbreviated as CNE, an independent institution/body that organizes national elections, meaning that the Comissão Nacional de Eleiçoes (CNE) is one of the central institutions in Timor Leste tasked with supervising, organizing, managing and organizing General Elections as an instrument to realize people's sovereignty, form a legitimate government and as a means of articulating people's aspirations and interests. Civic education to increase community participation in general elections. Active participation of citizens in election activities is one measure of the effectiveness of the democratization process. This study aims to analyze and describe the Role of Civic Education to Increase Community Participation in the Timor Lese Presidential Election. The method used is descriptive research with a qualitative approach. Data collection techniques include observation, document study, and interviews, while data analysis techniques include the stages of data collection, data reduction, data presentation, and drawing conclusions. The theory of Bruce J. Cohen (1992) is the basis for the analysis in this study. The focus of the study is on indicators (1) Acted Role, (2) Prescribed Role. (3) Role Model. Civic Education which is very much needed in the midst of the urgency of democracy, where the values ​​and principles of democracy regarding general elections will be organized by the Comissão Nacional de Eleições (CNE) to voter participation through a program to socialize the stages of the Election and provide an understanding of political education to the community.